PERGUMULAN KEBATINAN JAWA MEMAKNAI KEHADIRAN YESUS KRISTUS - Antonius Kurnia Andrianto (Jurnal Teologi (Journal of Theology), 2016)
The local Church of the Archdiocese of Semarang (KAS) grows and develops in the Javanese culture. Before their conversion to Catholicism, many local Catholics held Kebatinan, a Javanese religious tradition, as their religion. Even after their conversion, some of them continue to practice some forms of the Javanese mysticism. In order to give a space for Catholics who are practicing such a mysticism, a forum called "Temu Kebatinan" which discusses themes of Javano-Catholicism was established. However, Javano-Catholics find themselves caught in the middle between living a more puritanical (Western) Catholicism and a more accommodative stance toward the Javanese culture. They find things that stand in harmony with their Catholic faith, but they also consider some of these practices as inappropriate, even syncretic. This article examines how the followers of "Kebatinan" interpret and navigate these tensions, especially to understand the special role of Jesus Christ.